The role of monsoon low‐level jet in modulating heavy rainfall events. (21st December 2017) - Xavier, Anu; Kottayil, Ajil; Mohanakumar, K.; Xavier, Prince K.
ABSTRACT: Monsoon low‐level jet (MLLJ) is an important component of Asian summer monsoon circulation, which is responsible for large‐scale distribution and variability of rainfall over the Indian subcontinent. The evolution of MLLJ characteristics prior to heavy rainfall days and its changes which lead to instances of heavy rainfall over the south‐western coast of India are studied. The European Centre for Medium Range Weather Forecasts (ECMWF) re‐analysis data and India Meteorological Department (IMD) rainfall data during 1979–2007 were used for this study. It is found that the MLLJ core speed, westerly wind depth, zonal water vapour flux, horizontal wind shear and cyclonic vorticity show a steady increase towards the day of heavy rainfall and gradually decrease thereafter. The intensification of these parameters not only brings in abundant moisture but also triggers convection, thereby resulting in the formation of heavy rainfall during monsoon season. The large‐scale advection of moisture brought about by strengthening of MLLJ is shown to be a prerequisite for heavy rainfall over the Indian subcontinent. An interesting result of this study is that heavy rainfall days may have some predictability by continuous monitoring of the progression of MLLJ. Abstract : Spatial evolution of zonal water vapour flux (kg s −1  m −1 ) on (Day 0) or prior to heavy rainfall events.